Emotional education in primary school: A learning for life - Sepúlveda Ruiz, María del Pilar; Mayorga Fernández, María José; Pascual Lacal, Rocío (Education Policy Analysis Archives, 2019)
Due to the social changes that are currently taking place, schools must attend to the emotional training of students. Part of a larger European project on student emotions and current conditions of education systems from participating partners, this study shows the results obtained in Spain (Malaga) for a period of 6-10 years. Specifically, the authors conducted a qualitative study based on the affective dimension of education. In total, 17 teachers participated. The results show that the curriculum is focused on the cognitive dimension, leaving aside the emotional dimension to existing legislation that explicitly stipulates that dimension. Schools should, however, should contemplate their educational function concerning the holistic development of its students, and this process should be designed and implemented on the basis of promoting all dimensions of the person.